2013
DOI: 10.1017/s0021859612001025
|View full text |Cite
|
Sign up to set email alerts
|

Use of fluorescence-based sensors to determine the nitrogen status of paddy rice

Abstract: SUMMARYThe environmental concern about diffuse pollution from nitrogen (N) fertilizers has led to increased research on the diagnosis of crop N status. The SPAD chlorophyll (Chl) meter is the most commonly used tool for rice (Oryza sativa L.) N status diagnosis, but measurements are conducted at a specific point and readings are affected by different leaf positions. Many measurements per plant must be taken in order to increase the accuracy of N status diagnosis, which limits its application. The present paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
20
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
9
20
4
Order By: Relevance
“…The fluorescence indices, SFR (index of chlorophyll content) and NBI (index of N sufficiency) measured with the Multiplex 3 sensor, were strongly related with crop canopy N density (CND) for most of the measurements made throughout the winter wheat growth stages. These results from this study are in agreement with recent reports which describe the potential of fluorescence sensing methods for the monitoring of crop N status of other crop species [58][59][60], indicating that fluorescence indices are also suitable to determine the N status and grain quality in winter wheat.…”
Section: Discussionsupporting
confidence: 92%
“…The fluorescence indices, SFR (index of chlorophyll content) and NBI (index of N sufficiency) measured with the Multiplex 3 sensor, were strongly related with crop canopy N density (CND) for most of the measurements made throughout the winter wheat growth stages. These results from this study are in agreement with recent reports which describe the potential of fluorescence sensing methods for the monitoring of crop N status of other crop species [58][59][60], indicating that fluorescence indices are also suitable to determine the N status and grain quality in winter wheat.…”
Section: Discussionsupporting
confidence: 92%
“…Strong relationships between the Multiplex indices (SFR_G, SFR_R, BRR_FRF, FLAV, NBI_G, and NBI_R) measured in the OG mode and the five N indicators were achieved with low RE and high R 2 values (Table 4, Figure 3). This finding conforms to previous research results in this field [26,42,55,56]. Many studies confirmed SFR was a good fluorescence index for chlorophyll content monitoring [24,38,57].…”
Section: Multiplex Measurement Modes and Estimation Of Crop N Indicatsupporting
confidence: 92%
“…In addition, they found leaf-scale (LS) Multiplex measurements were better related to N treatments than the Multiplex readings made from a small distance above the canopy (AC). Li et al [42] reported that both leaf-based SPAD and canopy Multiplex indices could be used to predict rice leaf N contents. The on-the-go (OG) measurement mode means placing the sensor probe in the canopy close to the blade and continuously collecting data during the move.…”
mentioning
confidence: 99%
“…SFR_R is a simple fluorescence ratio, which reflects the leaf chlorophyll content based on the reabsorption of chlorophyll fluorescence (Gitelson, Buschmann, and Lichtenthaler 1999); FLAV is the logarithmic ratio of FRF_R to FRF_UV, which reflects the polyphenol content and NBI_R (FRF_UV/ RF_R) is the ratio of chlorophyll to polyphenols. Details about the fluorescence-based indexes can be found in an earlier report prepared by the authors (Li et al 2013). Thirty measurements were conducted in each plot, and the average was calculated after the acquisition of the aerial images.…”
Section: Nitrogen Balance Index Of the Rice Canopymentioning
confidence: 99%
“…The chlorophyll to polyphenol ratio, known as the nitrogen balance index (NBI), should accentuate the differences between the levels of crop nitrogen deficiencies because the chlorophyll and the polyphenols are inversely dependent on the crop nitrogen nutrition status (Cartelat et al 2005). Furthermore, by using fluorescencebased indexes at the canopy level, the potential deviation caused by the aforementioned leaf positions and the leaf age can be avoided (Li et al 2013).…”
Section: Introductionmentioning
confidence: 99%